Sensitization trends after renal allograft failure: the role of DQ eplet mismatches in becoming highly sensitized. Issue 1 (15th December 2015) - Singh, Pooja; Filippone, Edward J.; Colombe, Beth W.; Shah, Ashesh P.; Zhan, Tingting; Harach, Mary; Gorn, Chad; Frank, Adam M.
Abstract: Sensitization following renal allograft failure (AF) is highly variable. Some patients remain non‐sensitized (NS), while others become highly sensitized (HS). We studied 66 NS patients who experienced AF after initial kidney transplantation. Post‐failure, two main groups of NS panel reactive antibody (PRA) class I and II <10% and HS patients (PRA class I or II ≥80%) were identified. The impact of acute rejection (AR), immunosuppression withdrawal (ISW) at AF, allograft nephrectomy, graft intolerance syndrome (GIS), and both standard serologic and eplet‐based mismatches (MM) in inducing HS status after failure was examined. Late PRA testing post‐failure revealed 18 patients remained NS and 34 patients became HS. African American recipients, ISW at AF, DQB1 eplet MM, and presence of GIS were associated with becoming HS. Presence of total zero eplet MM, zero DQA1/B1 eplet MM, continuation of immunosuppression after failure, and a hyporesponsive immune status characterized by recurrent infections were features of NS patients. DQ eplet MM represents a significant risk for becoming HS after AF. Studies comparing ISW vs. continuation in re‐transplant candidates with high baseline DQ eplet MM burden should be performed. This may provide insights if sensitization post‐AF can be lessened.